New approaches to treating pain. Issue 4 (15th February 2016) - Wolkerstorfer, Andrea; Handler, Norbert; Buschmann, Helmut
Graphical abstract: After 100 years of pain research—old scaffolds, minor improvements? Abstract: Pain is the most common reason for patients seeking medical care resulting in an estimated world market for analgesics of more than USD 50 billion. Pain is a highly complex, heterogeneous and dynamic process characterized by specific patterns of phenotypic sensory neuronal change. Current treatment options for pain include opioids and non-opioid analgesics, acetaminophen and non-steroidal anti-inflammatory drugs and other drug classes such as antidepressants and anticonvulsants and a combination thereof. Novel approaches are focusing on the optimization of side-effect profiles of opioid based analgesics, the improvement of selectivity for specific opioid receptors, or by addressing molecular gateways implicated in pain. Promising candidates in development target various types of voltage-gated ion channels and receptors for capsaicin and analogs. Currently, after decades of pain research it has to be stated that the assessment, prevention and treatment of pain in industrialized countries as well as in low-income and middle-income countries are neither adequate nor equitable. Further research is needed so that specifically chronic pain control can be improved and individualized.